Taking Libraries’ Cultural Content to the User: Approaches and Experiences from the EEXCESS Project - Borst, Timo; Lehmann, Maren; Pianos, Tamara; Witt, Nils (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Before the advent of the internet users had to physically visit libraries and other cultural institutions in order to search, find and access content. With the emergence and massive use of the World Wide Web and associated tools and technologies this situation has changed drastically. If content is to be found and used, it must be present where users do their daily digital work. The aim of the EU project EEXCESS (http://eexcess.eu/) is to inject the content into the working environments of the users. In this paper, we show some of the approaches, use cases and technical implementations we developed in the project.